2020
DOI: 10.18632/aging.103506
|View full text |Cite
|
Sign up to set email alerts
|

High serum uric acid is associated with increased arterial stiffness in hypertension

Abstract: Serum uric acid level has been found to be associated with cerebrovascular diseases. However, whether serum uric acid level is a risk factor for arterial stiffness in the hypertension population is unclear. This study was designed to determine the relationship between serum uric acid level and arterial stiffness in the hypertension population. A total of 10450 participants were evaluated for the risk of arterial stiffness. Brachial-ankle pulse wave velocity (baPWV) was assessed, and high baPWV was determined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We found the significant positive correlation between the IMC thickness and the serum levels of UA, hsCRP, despite controversial previous data on this topic. Ramirez et al [11,12] reported an independent association between UA and the IMC thickness, while Songand et al [13,14] did not find such a correlation, which may be related to different characteristics of the sample and the methodological approaches chosen.…”
Section: Discussionmentioning
confidence: 96%
“…We found the significant positive correlation between the IMC thickness and the serum levels of UA, hsCRP, despite controversial previous data on this topic. Ramirez et al [11,12] reported an independent association between UA and the IMC thickness, while Songand et al [13,14] did not find such a correlation, which may be related to different characteristics of the sample and the methodological approaches chosen.…”
Section: Discussionmentioning
confidence: 96%
“…Of note, Hcy and UA are thought to mediate adverse cardiovascular events through arterial stiffness [ 16 , 40 ]. Previous population-based studies have shown that high Hcy or high UA is an independent risk factor of arterial stiffness [ 19 , 41 ]. However, studies on the effect of Hcy and UA on arterial stiffness are mostly limited to people with high risk of cardiovascular diseases, such as hypertension, diabetes, and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive patients with hyperuricemia also presented with higher CF-PWV than hypertensive patients without hyperuricemia [ 11 ]. In a large hypertensive population from China comprising 10,450 participants, of whom > 90% were receiving antihypertensive agents and ~ 50% were current smokers, serum uric acid was a risk factor for higher brachial-ankle PWV in men and women [ 38 ]. As a major difference to our study, medicated hypertensive subjects were included in the analyses of the above studies [ 11 ].…”
Section: Discussionmentioning
confidence: 99%